The role of mental exercise in optimizing athlete performance: A systematic review of cognitive and psychological interventions - Piri, Nolfie; Ihsan, Fadli; Alfrets Makadada, Fredrik; Pandeleke, Tony (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study aimed to evaluate and analyze the role of mental training in optimizing athletes’ performance, with a focus on cognitive and psychological interventions. The study was conducted using a systematic review method, using inclusion and exclusion criteria to select relevant articles from various databases, including PubMed, Scopus, and Google Scholar. Of the 26 studies that met the criteria, it was found that mental training significantly improved the performance of athletes in various sports. Cognitive interventions, such as visualization and focus techniques, have been shown to be effective in improving concentration and reducing anxiety. In addition, psychological interventions, including stress management and confidence development, showed a significant positive impact on athletes’ motivation and mental resilience. These results show that mental training not only contributes to improved physical performance, but also facilitates the mental development necessary to compete at a high level. These findings underscore the importance of integrating mental training in athletes’ training programs to reach their maximum potential. Recommendations for further research include the exploration of new techniques and the development of mental training programs tailored to the specific needs of athletes. Thus, mental exercise can be recognized as an integral part of a holistic approach to improving sports performance.